The evolution of partial reproductive isolation as an adaptive optimum. (25th November 2019) - Servedio, Maria R.; Hermisson, Joachim
Abstract: Decades of theoretical work on the evolution of adaptive prezygotic isolation have led to an interesting finding—namely that stable partial reproductive isolation is a relatively common outcome. This conclusion is generally lost, however, in the desire to pinpoint when exactly speciation occurs. Here, we argue that the evolution of partial reproductive isolation is of great interest in its own right and matches empirical findings that ongoing hybridization is taxonomically widespread. We present the mechanisms by which partial reproductive isolation can be a stable evolutionary endpoint, concentrating on insights from theoretical studies. We focus not on cases in which hybridization results from constraints imposed by ongoing migration or mutation, but on the intriguing idea that partial reproductive isolation may instead be an adaptive optimum. We identify three general categories of selective mechanisms that can lead to partial reproductive isolation: context‐dependent hybrid advantage, indirect selection due to the varying actions of sexual selection in different geographic contexts, and a balance of costs of choosiness with indirect selection for stronger mating preferences. By any of these mechanisms, stable partial reproductive isolation can potentially provide a robust evolutionary alternative to either complete speciation or population fusion.